Analysis of the Achievement of Zakat Distribution and Utilization by the BAZNAS from the Perspective of Maqashid Syariah Jaseer Auda - A'immatur Rosidah; Lathifah Sholatiah; Nurul Lailaturrokhmah (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
This article aims to evaluate the effectiveness of zakat property distribution and utilization by the National Amil Zakat Agency (BAZNAS) in contributing to poverty alleviation and community welfare in Indonesia. The research adopts a qualitative method with an empirical-normative approach. The subject of this study is BAZNAS, focusing on its ZIS-DSKL programs during 2023–2024. Data were collected through secondary sources, including official reports, academic literature, legal documents, and online publications. The analysis uses a content analysis method combined with Jasser Auda’s maqashid al-shariah theory, which emphasizes development and human rights as essential objectives of Islamic law. The results show that 93–94% of zakat funds were distributed for temporary, consumptive assistance, while only 6–7% were directed toward economic empowerment. This pattern reflects a limited contribution to sustainable mustahiq independence and indicates that the current distribution strategy aligns more with classical protective goals than progressive development-oriented objectives. Academically, this study contributes to the discourse on zakat reform by offering a theoretical framework for evaluating zakat policy effectiveness based on contemporary maqashid thinking.Keywords: Zakat Distribution; Utilization; BAZNAS; Maqashid al-Shariah; Jasser Auda.